2021
DOI: 10.22271/23487941.2021.v8.i6a.570
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal potential of certain plant extracts of the family Lamiaceae against Anopheles subpictus (Diptera: Culicidae)

Abstract: The present study was undertaken to check and compare the virtue of plant extracts in relation to larvicidal activities against Anopheles subpictus. The lethality and toxicity of methanolic and aqueous extracts of Ocimum sanctum, Ocimum basilicum, Leucas aspera and Coleus amboinicus to early 4 th instar larvae of A. subpictus were determined in the laboratory. All plant extracts of Lamiaceae showed moderate effect against the larvae of A. subpictus after 24 hours exposure as evidenced by low lethal concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Identifcation of potential insecticides and repellents from natural product resources, such as plant extract and essential oils is one solution for the abovementioned problems. Previous studies have demonstrated that members of the genus Leucas possess larvicidal [9][10][11][12], ovicidal [13], and repellent [14] activities. Terefore, the present study was designed to investigate the larvicidal, ovicidal, and repellent activities of the essential oil of leaves of Leucas stachydiformis (Hochst.…”
Section: Introductionmentioning
confidence: 99%
“…Identifcation of potential insecticides and repellents from natural product resources, such as plant extract and essential oils is one solution for the abovementioned problems. Previous studies have demonstrated that members of the genus Leucas possess larvicidal [9][10][11][12], ovicidal [13], and repellent [14] activities. Terefore, the present study was designed to investigate the larvicidal, ovicidal, and repellent activities of the essential oil of leaves of Leucas stachydiformis (Hochst.…”
Section: Introductionmentioning
confidence: 99%
“…Identi cation of potential insecticides and repellents from natural product resources, such as plant extract and essential oils is one solution for the above problems. Previous studies have demonstrated that members of the genus Leucas possess larvicidal [9][10][11][12], ovicidal [13] and repellent [14] properties against different stages in the life cycle of mosquito vectors. Therefore, the present study was designed to investigate the larvicidal, ovicidal, and repellent activities of the essential oil of leaves of Leucas stachydiforms (Hochst.…”
Section: Introductionmentioning
confidence: 99%